Proyecto de factibilidad para la creación de un restaurant de comidas típicas de la amazonía, en la parroquia Dayuma, cantón Francisco de Orellana, provincia de Orellana - Armas Ramírez, Enid Alexandra (2014)
Ecuadorian society has progressed in parallel with other companies within business field, from the creation of family businesses to large companies due to the various market opportunities offered by society in general. The entrepreneurial vision is important for the productive field of society as it will help in the near future to a new country's economic recovery, accepting certain changes that the sector in question demands competitively in each of the lines that production units offered. This project aims DETERMINE THE TECHNICAL FEASIBILITY, ECONOMIC, FINANCIAL AND ADMINISTRATIVE OF A TYPICAL MEALS ON AMAZON Dayuma PARISH, Canton Francisco de Orellana Province Orellana, leveraging existing resources in the locality RESTAURANT. To carry out research population segmentation helped find a way to deal with the complex and diverse demands of people did. For each of the requirements of market surveys of potential consumers, and vendors of locally applied. Emphasizing everything mentioned above this project was obtained the following main results: The market study was conducted in the parish Dayuma resulting in a potential demand of 7,183 people who eat typical food and a real demand for 7,183 people and 7,183 effective demand through analysis of supply and demand could be determined product based on an unmet demand for 589006, the same as is obtained between the projected demand less supply. To produce the product of excellent quality raw material, procured will be used in the local market; the selling price of the typical Amazon dish will be comfortable and affordable for everyone to get citizenship will be promoted every day from 10 am to 12 am through a radius of the town. The location factors that were taken to the location of the company were the main raw material supply, roads, utilities, labor and market. As regards the legal aspect of the company is established as a limited company, with the company name RESTAURANT TABLE OF STONE CULTURAL, the same that will be devoted to the production and sale of Amazon dishes. With the economic-financial study the price of a typical dish of the Amazon is at an average of $ 3 retail including established 100% profit, so does the balance point of the first year was determined in terms of capacity installed the 54.17%, and according to sales having 67,385 cash flow for the first year of $. 124,394. This project will have a 53.40% equity by investors up to $ 10,000.00 and 46.60% with credit to National Development Bank to an interest rate of 11.20% per annum for five. Through the financial evaluation indicators of the net present value (NPV) of $ 72,065.00 was determined which ensures performance in the value of the company at the end of its useful life (5 years), with an Internal Rate of Return (IRR) on investment of 106,64% while a Benefit Cost Ratio at $ 1.47, as profit for every dollar invested, the Capital Recovery Period (PRC) is 2 years, 7 months and 27 days the project and accept an increase in the costs of 31% and a decrease in revenue of 8,8%. The detailed implementation of each stage based on the results of this investment project demonstrates the feasibility of the feasibility of execution, largely filling the expectations of future consumers.